RANCANG BANGUN MEMONITOR ARUS DAN TEGANGAN SERTA KECEPATAN MOTOR INDUKSI 3 FASA MENGGUNAKAN WEB BERBASIS ARDUINO DUE - Wilutomo, Resnu Mauliyana Mukti; Yuwono, Teguh (Vocational School Diponegoro University, 2017)
Resnu Mauliyana Mukti Wilutomo, Teguh Yuwono, 3 phase induction motor must work well and safely. Many types of interference have the potential to interfere with motor performance or even damage the motor itself, including due to power instability which includes imbalance between phase voltages and more phase currents. Monitoring an industrial activity especially monitoring the protection system is very important, it is intended that the disturbance that occurs in the 3 phase induction motor can be analyzed for the value and type of interference. Rapid technological development requires a monitoring system that is practical, fast and accurate. Sensors installed on this device are current sensors, voltage sensors, and speed sensors. The read, current, voltage and speed will be used as input signals to Arduino using the ADC (Analog to Digital Converter) process, Arduino programming uses C ++ language. ESP8266 wifi module) will upload the data from the ADC (Analog to Digital Converter) process to the database which is then displayed on the web using the available internet network. The web programming language used is PHP. This tool makes it easy to monitor a 3 phase induction motor because it can be done anytime and anywhere. There was a difference of Â± 0.24A between the Tang Ampere measuring instrument and reading on the web. A Â± 4V difference occurs between the Multimeter measuring instrument with readings on the Web. The maximum speed of the 3-phase induction motor with no load is 22Rpm between the tachometer gauge and the web display.